2019
DOI: 10.1016/j.solmat.2019.110128
|View full text |Cite
|
Sign up to set email alerts
|

In−situ monitoring Poly(3-hexylthiophene) nanowire formation and shape evolution in solution via small angle neutron scattering

Abstract: The crystallization of poly(3-hexylthiophene) (P3HT) to form nanowires has attracted considerable interest because this process significantly increases the hole mobility when compared to amorphous P3HT, leading to improved performance in photovoltaic and other organic electronic devices. However, full characterization of the crystallization self-assembly of the polymer chains in solution has not been achieved yet, due to limited use of in − situ not destructive techniques. Here, we investigate the ageing-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…Figure a–c shows the transmission spectra of the block copolymers where the three characteristic vibronic shoulders of P3HT films at λ = 520 nm, λ = 554 nm, and at λ = 610 nm can be immediately identified. [ 74,75 ] This is expected since the block copolymer contains P3HT. It is worth noting that PSS absorbs in the ultraviolet region (λ < 300 nm) of the electromagnetic spectrum [ 76 ] and therefore, does not show in these spectra.…”
Section: Resultsmentioning
confidence: 93%
“…Figure a–c shows the transmission spectra of the block copolymers where the three characteristic vibronic shoulders of P3HT films at λ = 520 nm, λ = 554 nm, and at λ = 610 nm can be immediately identified. [ 74,75 ] This is expected since the block copolymer contains P3HT. It is worth noting that PSS absorbs in the ultraviolet region (λ < 300 nm) of the electromagnetic spectrum [ 76 ] and therefore, does not show in these spectra.…”
Section: Resultsmentioning
confidence: 93%
“…Although a flow field is inevitably applied during P3HT processing, a few theoretical and experimental contributions have been dedicated to the flow‐induced conformation transition of P3HT in solution. It is generally accepted that the coil‐to‐rod transition and π‐π stacking of the rods during the P3HT crystallization process lead to a bathochromic shift in the UV‐vis absorption peak and the appearance of new vibrational peaks . Figure shows the UV‐vis spectra of a pristine solution, a resided solution, and a sheared solution of P3HT in toluene with the concentration as 0.04 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Bastianini et al investigated the aging‐driven formation and evolution of P3HT nanostructures in chlorobenzene solution using small‐angle neutron scattering and UV‐vis spectroscopy. They found the initial states for P3HT chains were the random coils, then the coil straightened to form rods, these rods subsequently π‐π stacked to form two‐dimensional lamellae, which further stacked to create nanowires . Currently, coil‐to‐rod transition and π‐π stacking of the rods are widely accepted as two elemental processes of P3HT crystallization in solution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-angle neutron scattering (SANS) can be used to study the microstructure, especially size, shape and dynamics of their components. [114,117,170,171] Dadmun et al [164] using the SANS to characterize the morphology and aggregation of the PCPDTBT:PCBM blends in different solvent annealing conditions. Due to the significant differences between PCPDTBT and PCBM in scattering length density, the scattering profile of Figure 5G showed that the scattering strength of as-cast film (AC) is very weak, which suggests that the film is homogeneous and the phase separation is not obvious, while the scattering pattern of the blends with the solvent annealing by oDCB exhibit enhanced scattering, indicating a phase separation of the fullerene and polymer in the blend.…”
Section: Characterization Tools Of Aggregated Structuresmentioning
confidence: 99%